Personnel management in government agencies and nonprofit organizations - Dresang, Dennis L. (New York Routledge, 2017)
"The long-awaited new edition of this highly praised text includes full coverage of policy issues and professional practice in nonprofit organizations, as well as at federal, state, and local levels of government. Retaining its accessible writing style, this sixth edition: examines the latest management theories (such as employee engagement and motivation) and current issues including disability, privatization, merit systems, and family and medical leave; roots the discussion in public policy issues, providing students with a better understanding of the actors involved and the broader context of personnel administration; provides abundant pedagogical tools, including learning objectives, summaries, and discussion questions, to guide student understanding and foster critical thinking; includes exercises and case studies throughout the book for individual or group work, helping students apply public personnel management concepts to real world situations. In addition to full coverage of the increasingly important role of personnel management in nonprofit organizations, this new edition has been thoroughly updated to include timely material on the effects of the 2008 global recession, public service contracting, public sector unions, security concerns, performance measurement, remote management, management of volunteers, the challenges and opportunities of developing an organizational culture, and lessons from the experiences of countries around the world. This is a textbook that is ideally suited to prepare students to manage people, effectively, whether in government, nonprofit organizations, NGOs, or in the private sector."--Provided by publisher
Includes bibliographical references and index.
Keywords: Civil service -- Personnel management